Status Gizi Pada Balita Usia 0-5 Tahun di Desa Teupin Gapeuh Kecamatan Tanah Pasir, Kabupaten Aceh Utara - Srie Wahyuni; Quranayati Quranayati; Rieni Yuliarti; Zahratul Rahmi; Irrazatul Azmi (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
The nutritional status of toddlers is an important indicator that reflects the level of public health in a region. This study aims to analyze the nutritional status of children aged 0–5 years in Teupin Desa Teupin Gapeuh Kecamatan Tanah Pasir Kabupaten Aceh Utara. This research employed a descriptive quantitative method using secondary data obtained from health records and posyandu (integrated health post) reports. The study involved a total of 60 children under five, consisting of 33 boys and 27 girls. The findings revealed that based on the weight-for-age (W/A) index, 81.7% of children had normal nutritional status, 13.3% were undernourished, and 3.3% were severely undernourished. Based on height-for-age (H/A), 90.0% were normal, 5.0% were short, and 3.3% were very short. According to the weight-for-height (W/H) index, 83.3% were normal, 11.7% were undernourished, and 5.0% were at risk of overweight. Furthermore, the prevalence of stunting, wasting, and underweight were 8.3%, 11.7%, and 16.7% respectively. These results indicate that although most children have normal nutritional status, some still experience nutritional deficiencies that require special attention. Therefore, health workers and local governments need to strengthen nutrition education programs, increase community awareness of balanced nutrition, and improve monitoring of child growth to prevent malnutrition in the area